2019
DOI: 10.1371/journal.pone.0217280
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric assessment of the French European Developmental Coordination Disorder Questionnaire (DCDQ-FE)

Abstract: Background The Developmental Coordination Disorder Questionnaire’07 (DCDQ’07) is a parent-report measure to identify children at risk for Developmental Coordination Disorder (DCD). We developed a French version of the DCDQ’07 (DCDQ-FE) that has shown excellent inter-language reliability (intraclass correlation coefficient (ICC) = 0.91) and is culturally relevant for use in European countries. The aims of this study were to examine the internal consistency, test-retest reliability, construct validi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
(72 reference statements)
1
15
0
2
Order By: Relevance
“…In line with previous studies, findings from this further validation work report higher internal consistency values for the DCDQ-ES total scale and for the three subscales [24][25][26][27][28][29][30][31]. Cronbach's alpha values in other validation studies in European, Asian and Latin American populations range from 0.89 to 0.96 [24][25][26][27][28][29][30][31], demonstrating that the DCDQ is a reliable tool for assessing motor coordination and probable DCD.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In line with previous studies, findings from this further validation work report higher internal consistency values for the DCDQ-ES total scale and for the three subscales [24][25][26][27][28][29][30][31]. Cronbach's alpha values in other validation studies in European, Asian and Latin American populations range from 0.89 to 0.96 [24][25][26][27][28][29][30][31], demonstrating that the DCDQ is a reliable tool for assessing motor coordination and probable DCD.…”
Section: Discussionsupporting
confidence: 88%
“…However, sensitivity and specificity values for the clinical proposed Spanish cut-off were similar with that of the original DCDQ and other cross-cultural adaptations [23,[25][26][27]30,35]. For instance, sensitivity and specificity of the German version of the DCDQ for a clinic sample was 72.7% and 95%, while these values decreased to 30% and 86.7% in a community sample [25].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Previous studies have demonstrated that DCD-related questionnaires aimed to identify risk of DCD must undergo a rigorous process to ensure its cross-cultural equivalence prior to testing their psychometric properties in the target population in order to verify that the items are culturally relevant, semantically correct and easy to interpretate [ 19 , 20 , 23 , 24 , 25 , 26 , 27 ]. Thus, it is necessary to conduct a cross-cultural adaptation of the AAC-Q into European Spanish before performing a comprehensive psychometric validation study and developing reference norms in the Spanish population.…”
Section: Introductionmentioning
confidence: 99%